Fungal infection involvement in primary biliary cirrhosis: A review of 2 cases - Wang, Yanyan (Exp Ther Med, 2017)
The present study aimed to analyze the imaging, clinical and pathological features of fungal infection involvement in primary biliary cirrhosis (PBC) by retrospectively analyzing and reviewing the features of two patients with fungal infection involvement in PBC. Both patients were female. One patient had a confirmed diagnosis of PBC. The other patient had confirmed Sjogren syndrome and PBC. The two cases of PBC were infected with fungal infection after treatment with hormonal and immunosuppressive agents. RCR of sputum confirmed Pneumocystis spp. infection in the patient with PBC alone. The mucormycosis infection was confirmed in the other patient after pathological examination of a renal biopsy. The state of the illnesses progressed quickly and both patients ultimately succumbed to their conditions. The patient prognosis of fungal infection involvement PBC is poor. Patients treated with long-term hormone and immunosuppressive agents should be monitored.